(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article highlights the psychological aspects of the professionalization of future teachers in the process of training. The essence of modeling the deontological profile of future specialist teachers in modern society is noted. The author pays special attention to the development of psychological and pedagogical meta-competencies of students. The significance of psychological and pedagogical support of the deontological development of youth in higher education institutions is determined. The author gives the results of an empirical study of the ideas of future teachers on the deontological profile of the teacher. The relevance of systemic modeling of the deontological profile of a person in the dimensions of training is proved.